Effects of two protease inhibitors from Bauhinia bauhinoides with different specificity towards gut enzymes of Nasutitermes corniger and its survival. (May 2019) - Ferreira, R.S.; Brito, M.V.; Napoleão, T.H.; Silva, M.C.C.; Paiva, P.M.G.; Oliva, M.L.V.
Abstract: Two recombinant protease inhibitors from Bauhinia bauhinioides, rBbKI (kallikrein inhibitor) and rBbCI (cruzipain inhibitor) were evaluated for insecticidal activity against workers and soldiers of Nasutitermes corniger (order: Isoptera; family: Termitidae) through the inhibitors' effect on the insect's gut enzymes. The inhibitor rBbKI was more effective than rBbCI in inhibiting the termite's gut enzymes. The kallikrein inhibitor showed termiticidal activity in workers with an LC50 of 0.9 mg mL −1 after 4 days. Conversely, rBbKI did not affect the survival of soldiers and rBbCI did not show termiticidal activity against N. corniger . The two inhibitors showed different specificity towards the termite's gut enzymes, representing interesting tools to characterize N. corniger enzymes. The different effects of rBbKI and rBbCI on the termite's enzymes and survival may be linked to slight structural differences between these inhibitors. Highlights: Inhibitors of B. bauhinioides with high structural similarity but different deleterious activity. rBbKI is a potent inhibitor of the digestive tract enzymes of Nasutitermes corniger. rBbCI can be used in conjunction with rBbKI when the insect overcomes the action of the enzymes inhibited by rBbKI. rBbKI can be genetically incorporated into the genome of trees of commercial value.